Modelling of aerodynamic flutter on a NACA 4412 airfoil with application to wind turbine blades. (2013) - Ramdenee*, Drishtysingh; Ilinca, Adrian; Minea, Sorin lon; Hussein, Ibrahim
The study of aeroelastic phenomena on Wind Turbines (WTs) has become a very important issue when it comes to safety and economic considerations, as WTs tend towards gigantism and flexibility. At the Wind Energy Research Laboratory (WERL), several studies and papers have been conducted and published, all focusing on Computational Fluid Dynamics (CFD model) approaches to model and simulate different aeroelastic phenomena. Despite the very interesting results obtained, CFD is very costly and is difficult to use directly for control purposes, due to the consequent computational time. This paper describes a complementary lumped system approach to CFD to model flutter phenomenon. This model is based on a Matlab-Simulink model that integrates turbulence characteristics as well as characteristics of aerodynamic physics. From this model, we elaborate on flutter eigenmodes and eigenvalues in an aim to apply control strategies and relate the ANSYS-based CFD modelling to the lumped system.